Simultaneous enhancement of strength and ductility in quaternary Ti–V–Al–B light weight shape memory alloys with high transformation temperature. (November 2020) - Yi, Xiaoyang; Wang, Haizhen; Sun, Kuishan; Zhang, Hua; Gong, Yifu; Gao, Zhiyong; Meng, Xianglong; Cai, Wei; Zhao, Liancheng
Abstract: In the present paper, the mechanical and functional properties of Ti–V–Al alloy were tailored by adjusting the boron (B) content. In addition, the effect of B content on the microstructure and martensitic transformation behaviors of Ti–V–Al alloys was also explored. The results indicated that the microstructure of Ti–V–Al alloys was sole α'' martensite phase, irrespective of the B content. B was completely soluble in Ti–V–Al alloy, as B content was not more than 0.01 at.%. Further increased B content not only promoted to the formation of TiB phase, but also resulted in the remarkable grain refinement. During heating process, the orthorhombic structure α'' martensite transformed into β phase with a body-centered cubic structure in one stage manner for all Ti–V–Al alloys containing different B contents. With the increased B content, the transformation temperature firstly decreased and then increased. Moderate B addition can improve significantly the mechanical properties and strain recovery characteristics of Ti–V–Al alloys owing to the perfect combination of solution strengthening, grain refinement, and precipitation strengthening of in-situ TiB phase. The maximum yield strength of 711 MPa can be obtained in 0.1 at.%B doped Ti–V–Al alloy with superior elongation of 18.5%. Moreover, it showed the largest recoverable strain of 5.1% under the condition of 6% pre-strain. Highlights: B addition can lead to the grain refinement and presence of TiB phase. B addition can maintain the higher transformation temperature of Ti–V–Al alloy and the reasons were explored. The higher strength and superior ductility can be simultaneously obtained in Ti–V–Al–B alloys. The origin of excellent mechanical properties in Ti–V–Al alloy doped B was explored.